PENGARUH PERSEPSI HARGA, DESAIN PRODUK, DAN PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MOBIL MITSUBISHI XPANDER (STUDI KASUS PT. NUSANTARA BERLIAN MOTOR MEDAN) - ATIKA AINI NASUTION (JURNAL ILMIAH SIMANTEK, 2020)
This research aims to know and analyze the influence of price perception, product design, and consumer preferences on thepurchasing decision of Mitsubishi Xpander (study case in PT Nusantara Berlian Motor Medan). This research is anassociative research. The population in this research are all consumers whoever bought Mitsubishi Xpander car in PT.Nusantara Berlian Motor Medan. Questionnaire used as the instrument in this research, within the interview anddocumentation. The data analyzed used descriptive method and quantitative that is double linear regretion with significancylevel 0.05. The F test result shows that of price perception, product design, and consumer preferences together has positiveand significant influence towards the dependent variable that is purchasingdecision.